Engineering and Analyzing Multicellular Systems Methods and Protocols - Sun, Lianhong; Shou, Wenying; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Engineering Multicellular Systems: Methods and Protocols, focuses on laboratory procedures used in recent efforts for constructing synthetic multicellular systems and their applications. In particular, constructing multicellular systems to form various microbial ecosystems has been extensively explored to examine evolution and interactions of microbial ecosystems, while co-cultures have emerged as an efficient tool to produce some complex chemical molecules. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Engineering Multicellular Systems: Methods and Protocols provides a comprehensive laboratory protocol reference for constructing multicellular systems for various applications.
Recent Progress in Engineering Human-associated Microbiomes -- Constructing Synthetic Microbial Communities to Explore the Ecology and Evolution of Symbiosis -- Combining Engineering and Evolution to Create Novel Metabolic Mutualisms Between Species -- Design, Construction and Characterization Methodologies for Synthetic Microbial Consortia -- An Observation Method for Autonomous Signaling-mediated Synthetic Diversification in Escherichia coli -- Integration-free Reprogramming of Somatic Cells to Induced Pluripotent Stem Cells (iPSCs) without Viral Vectors, Recombinant DNA and Genetic Modification -- Transformation of Bacillus subtilis -- Culturing Anaerobes to use as a Model System for Studying the Evolution of Syntrophic Mutualism -- Therapeutic Microbes for Infectious Disease -- Quantitative Measurement and Analysis in a Synthetic Pattern Formation Multicellular System -- Transcriptome Analysis of a Microbial Coculture in which the Cell Populations are Separated by a Membrane -- Identification of Mutations in Laboratory Evolved Microbes from Next-generation Sequencing data using breseq -- 3D-Fluorescence in situ Hybridization of Intact, Anaerobic Biofilm -- The Characterization of Living Bacterial Colonies Using Nano spray Desorption Electrospray Ionization Mass Spectrometry -- Modeling Community Population Dynamics with the Open-Source Language R -- Simulating Microbial Community Patterning using Biocellion.
Keywords: Biotechnology; Biochemical engineering; Biotechnology; Biochemical Engineering